2013
DOI: 10.4149/bll_2013_042
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thiopurine-S-methyltransferase genotype on the adverse drug reactions to azathioprine in patients with inflammatory bowel diseases

Abstract: Background and aims: The thiopurine drugs, azathioprine (AZA) and 6-mercaptopurine, are established in the treatment of infl ammatory bowel diseases (IBD). Polymorphisms in thiopurine S-methyltransferase (TPMT) gene have been associated with adverse drug reactions (ADRs) to AZA. Methods: The aim of this study was to evaluate TPMT polymorphisms and AZA-related toxicity in a Slovak cohort of 220 IBD patients treated with AZA. In every patient, the dose and duration of AZA therapy, concomitant 5-aminosalicylate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Azathioprine intolerance was not related to the presence of TPMT mutations, and hence, it was probably ascribable to high drug exposure. Similar observations have been done in systemic lupus erythematosus and inflammatory bowel diseases .…”
Section: Discussionsupporting
confidence: 83%
“…Azathioprine intolerance was not related to the presence of TPMT mutations, and hence, it was probably ascribable to high drug exposure. Similar observations have been done in systemic lupus erythematosus and inflammatory bowel diseases .…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, a randomised controlled trial comparing AZA monotherapy with AZA therapy combined with olsalazine showed significant lower mean WBC counts in the combination treatment group (4.65 ± 0.4 vs 4.05 ± 0.3) . Eight studies found no significant effect of concomitant 5‐ASA use on the development of TIL . In contrast, a threefold higher risk for leukopenia was found for concomitant 5‐ASA use after correction for baseline WBC count in multivariable regression analysis and a significant higher leukopenia rate in the concomitant 5‐ASA group compared to patients without concomitant 5‐ASA use were found in two Chinese cohort studies .…”
Section: Resultsmentioning
confidence: 91%
“…The association of TPMT genotype polymorphisms and TIL was assessed in 31 studies, the association of TPMT enzymatic activity and TIL in 12 (Table S1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations